Progress in the Application of Bronchoscopic Cryotherapy in Pediatric Pulmonary Diseases - Xiaofen Tao; Shuxian Li; Hujun Wu; Fang Jin; Guoping Jin; Lei Wu (Children)
Cryotherapy in interventional bronchoscopy is a new treatment modality which has recently been made available for the pediatric airway. Lack of experience and safety concerns have led to hesitant adaptation. The aim of this work was to elaborate on the application progress of cryotherapy in pediatric pulmonary diseases and also to assess indications, success rates, and complications of airway cryotherapy in children. In summary, cryotherapy via flexible bronchoscopy is a safe and feasible method. The application scope in pediatrics is similar to that in adults, and it is mainly used in airway obstructive diseases. However, it is primarily caused by benign conditions, and the interventional treatment mainly seeks to provide long-lasting symptomatic alleviation. Thus, prevention, treatment, and prognosis of long-term complications are issues that should be carefully considered in pediatric applications.